Optimalisasi Antena Mikrostrip Tiga Pita Untuk Penerapan Pada WLAN dan WiMAX - Muhammad Aditya Aditya Nikhaldo; Ikhwana Elfitri (Teknik Elektro Politeknik Negeri Padang, 2022)
Wired WLAN (Wireless Local Area Network) technology emerged as the most widely used network. WLAN is suitable for those who need internet. By using WLAN will be found various advantages for its users. Likewise with WiMAX (Worldwide Interoperability for Microwave Access) wireless technology, WiMAX basically has a function similar to WLAN, but with certain small differences. WLAN can cover one local area, in contrast to WiMAX which can cover a metropolitan area of ​​up to 50km. Antenna is an integral part of WLAN and WiMAX. This paper discusses a three-band microstrip antenna optimized for WLAN and WIMAX technology. The antenna consists of two layers of FR4 (epoxy) printed circuit board (PCB) with a thickness (h) of 1.6 mm, a dielectric constant (εr) of 4.4, and a dielectric loss factor (tan) of 0.02 with dimensions of 35 mm × 48 × 1.6 mm . This antenna is simulated using CST software. The design of the Studio Suite 2018 antenna is done by adjusting the size of the slot spacing, the length of the slot, the size of the ground clearance, and the size of the board length. In this antenna design, the slot size can be increased on the left side of the patch to increase the slot pitch for a deeper return loss, and the right side of the patch to increase the slot pitch for a shorter return loss. The results in the simulation process obtained good working frequency, bandwidth and return loss, the antenna can operate at the expected frequencies, namely 2.4 GHz, 3.2 GHz, 5.1 GHz with a return loss of -42 dB, -44 dB, - 31 dB. Bandwidths 114.4 MHz, 121.2MHz and 287.9MHz.